Accuracy of 18F-FDG PET/CT for primary tumor visualization and staging in T1 breast cancer. (January 2014) - Koolen, Bas B.; van der Leij, Femke; Vogel, Wouter V.; Rutgers, Emiel J. Th.; Vrancken Peeters, Marie-Jeanne T. F. D.; Elkhuizen, Paula H. M.; Valdés Olmos, Renato A.
Abstract Background. The aim of this study was to assess the accuracy of 18F-FDG PET/CT in T1 breast cancer regarding visualization of the primary tumor and the detection of locoregional and distant metastases. Methods. Sixty-two women with invasive T1 breast cancer underwent a PET/CT. Image acquisition of the thorax was done in prone position with hanging breasts, followed by whole-body scanning in supine position. Primary tumor FDG uptake was evaluated and compared with clinical and histopathological characteristics. Presence of locoregional and distant metastases was assessed and compared with conventional imaging procedures. Results. The primary tumor was visible with PET/CT in 54 (87%) of 62 patients, increasing from 59% (10/17) in tumors ≤ 10 mm to 98% (44/45) in tumors over 10 mm. All triple negative and HER2-positive tumors and 40/48 (83%) ER-positive/HER2-negative tumors were visualized. Sensitivity and specificity of PET/CT in the detection of axillary metastases were 73% and 100%, respectively. PET/CT depicted periclavicular nodes in two patients. Of 12 distant lesions, one was confirmed to be a lung metastasis, three were false positive, and eight were new primary proliferative lesions. Conclusion. Using optimal imaging acquisition, the majority of T1 breast carcinomas can be visualized with PET/CT. Specificity in the detection of axillary metastases is excellent, but sensitivity appears to be limited. Additional whole body imaging has a low yield in this specific patient group.